Population ageing in Malaysia: a mosaic of issues, challenges and prospects - Tengku Abdul Hamid, Tengku Aizan (Universiti Putra Malaysia Press, 2015)
The world is ageing, and in the next decade the growth of the aged population will be fastest in the developing countries. The number of older persons is expected to more than double globally from 841 million in 2013 to more than 2 billion in 2050. By then, nearly 8 in 10 of the world’s older population will live in less developed regions. Rapid population ageing in Malaysia can be attributed to the dramatic decline in fertility and mortality rates in tandem with longer life expectancy. Compared to the more developed countries, Malaysia has a rather short time to prepare for the transition into an aged nation. The older population aged 65 years or over will take only 23 years to double from 7 percent in 2020 to 14 percent in 2043. Like many other developing countries in the region, Malaysia is ageing at lower levels of development. All trends point towards a rapid demographic transition that is currently taking place as a “silent epidemic”. This inaugural lecture will focus on the trends of population ageing and the characteristics of the elderly in Malaysia from five (economic, health, social, psycho-spiritual, environmental) key domains. A discussion of the prospects and the way forward for population ageing in Malaysia is also presented. The ageing experiences of the population are influenced by normative age-grade, normative history-grade and non-normative events which make each cohort of aged distinct from another as the needs and demand of each cohort could be poles apart. The cross-cutting dimensions of ethnicity, gender, socio-economic background and geographical location will influence the trajectories across the life course as the situation of the aged differs by a unique combination of diverse past experiences. Malaysia is faced with a mammoth task of balancing the needs of a rapidly ageing society and at the same time promoting economic growth and development to fulfil the aspirations of becoming a high income nation. Ageing is a multidimensional, lifelong process with impact at both micro and macro levels to all members of the society. In Malaysia, the fast growth of the older population is not made opaque as the nascent knowledge on old age and ageing remains fragmented and unconsolidated. The use of empirical evidence in the planning of policies on ageing must be embraced at all levels of government and multi-sector stakeholders should collaborate closely to optimize the use of limited resources. The future of research on ageing in Malaysia lies in interdisciplinary studies with longitudinal panel data, uniting the fields of social, economic and psycho-gerontology, geriatrics, as well as gerontechnology. A society for all ages recognizes the need for lifelong development as policies designed for the younger population will also have a binding effect on the aged today as well as those of tomorrow.